Statistical Measures of the Competition in the Banking System - V. N. Salin; V. T. Sevruk; O. G. Tretiakova (Мир новой экономики)
The article describes the main statistical measures characterizing the key indicators of the competition level of the Russian banking system subjects countrywide and in the regional context. Utilizing common statistical tools of economic significance assessment of financial institutions, a dynamic analysis of banking competition level concentration was held. Dynamics of the main indicators, characterizing the saturation with financial and banking services of the Russian Federation regions, was assessed with regard to a long downward trend of the number of credit institutions. In order to analyze the availability of banking services in Russian regions, indices of total provision and relative attractiveness were evaluated. Quantitative and qualitative characteristics of level and dynamics of banking concentration were considered in depth, geographically and countrywide, with application of Herfindahl-Hirsehman index. Also, an analysis of concentration level of banking system assets was conducted. For this purpose, clusters of credit organizations distribution were considered depending on the value of their assets and their regional allocation.